How Can We Reduce the Overexploitation of the Mediterranean Resources? - Fiorentino, Fabio; Vitale, Sergio (Frontiers in Marine Science, 2021)
Based on the characteristics of the fishing sector (multispecies and multi-gears) and the stock status of main resources (overfishing and overexploitation), some suggestions to improve the sustainability of demersal and small pelagic fisheries in the Mediterranean are proposed. In fisheries exploiting single or few species, such as small pelagics and deep-water red shrimps, the adoption of a management system based on catch quota approaches is suggested. In the case of mixed fisheries exploiting species with very different biological traits, it is proposed to reduce the fishing effort to a level corresponding to the lower range of the “pretty good yield” of the main target species while improving the status of the most sensitive associated species, adopting technical measures to mitigate fishing mortality. The feasibility of the proposed approaches is briefly discussed, taking into account the different levels of development of the Mediterranean countries.